Malay martial arts - Mohd Zaki, Ahmad (2021)
Malay martial arts, Silat becomes one of the national heritages, registered under Intangible Cultural Heritage. Silat is an art that exists in the Malay Archipelago. Many studies about this art agree that Silat existed since the early of Langkasuka Kingdom (2nd century).